2021
DOI: 10.1039/d0ew00763c
|View full text |Cite
|
Sign up to set email alerts
|

Removal of PFASs from biosolids using a semi-pilot scale pyrolysis reactor and the application of biosolids derived biochar for the removal of PFASs from contaminated water

Abstract: This study focuses on the conversion of biosolids to biochar and its further use in adsorbing per- and polyfluoroalkyl substances (PFAS) from contaminated water. In particular, the study aims to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 58 publications
2
36
0
Order By: Relevance
“…Fortunately, most organic contaminants are destroyed with high efficiency during pyrolysis, by thermal degradation and volatilization followed by destruction during vapor combustion. This has been shown for PAHs (Zielińska & Oleszczuk, 2015), polychlorinated biphenyls (Bridle et al, 1990), per‐ and polyfluoroalkyl substances (PFAS; Kundu et al, 2021), microplastics (Ni et al, 2020), antimicrobials (Ross et al, 2016), antibiotics (Tian et al, 2019), antibiotic resistance genes (Kimbell et al, 2018), and hormones (estrogen; Hoffman et al, 2016).…”
Section: Biochar's Role In the Circular Economymentioning
confidence: 91%
“…Fortunately, most organic contaminants are destroyed with high efficiency during pyrolysis, by thermal degradation and volatilization followed by destruction during vapor combustion. This has been shown for PAHs (Zielińska & Oleszczuk, 2015), polychlorinated biphenyls (Bridle et al, 1990), per‐ and polyfluoroalkyl substances (PFAS; Kundu et al, 2021), microplastics (Ni et al, 2020), antimicrobials (Ross et al, 2016), antibiotics (Tian et al, 2019), antibiotic resistance genes (Kimbell et al, 2018), and hormones (estrogen; Hoffman et al, 2016).…”
Section: Biochar's Role In the Circular Economymentioning
confidence: 91%
“…Kim et al (2015) conducted pyrolysis experiments with wastewater solids at laboratory scale at 300°C and 700°C, finding no significant change of PFAS in the biochar. By contrast, Kundu et al (2021) demonstrated removal of all measured PFAS species in a municipal biosolid sample to non‐detect levels in char at temperatures ranging from 500°C to 600°C. Xiao et al (2020) investigated the thermal stability of several PFAS on granular activated carbon (GAC) in various reducing atmospheres.…”
Section: Unregulated Chemical Removal and Destructionmentioning
confidence: 92%
“…Kim et al (2015) conducted pyrolysis experiments with wastewater solids at laboratory scale at 300 C and 700 C, finding no significant change of PFAS in the biochar. By contrast, Kundu et al (2021) demonstrated removal of all measured PFAS species in a municipal biosolid sample to non-detect levels in char at temperatures ranging from 500 C to 600 C. Xiao et al (2020) investigated the thermal stability of several PFAS on granular activated carbon (GAC) in various reducing atmospheres. The study observed that more than 80% of perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS) adsorbed on GAC was converted to fluoride ions at temperatures exceeding 700 C, and concentrations of both compounds were reduced by more than 99.9%.…”
Section: Pfasmentioning
confidence: 99%
“…A research evaluated the adsorption of PFAS by biochars produced by the conversion of biosolids from wastewater treatment plants at three different temperatures (500, 550, and 600 °C), and compared their performance with a sawdust biomass biochar (Kundu et al, 2021). The 600 °C biochar (BSBC-600) had higher surface area, thus it was selected for the adsorption tests, where the results showed that for long-chain PFASs the adsorption was above 80%, while for short-chain PFASs was in the range of 19-27%.…”
Section: Adsorptionmentioning
confidence: 99%